HASH CONSTRUCTIONS THAT ARE SECURE AGAINST MULTICOLLISIONS - Luzhetskiy, Volodymyr; Baryshev, Yuriy (Scientific Works of Vinnytsia National Technical University, 2015)
The paper presents analysis of the attacks, based on finding multicollisions, and methods to counteract them. A generalized multi-pipe hash construction is proposed. Using this construction, the known methods of increasing hash constructions infeasibility are generalized and improved. A new approach to multicollisionresistant parallelized hashing design, formalized in the form of constructions, is proposed. Estimations of the proposed hash computing duration are presented.